Recent advances in carbon based nanosystems for cancer theranostics. (12th April 2017) - Augustine, Shine; Singh, Jay; Srivastava, Manish; Sharma, Monica; Das, Asmita; Malhotra, Bansi D.
Abstract : This review deals with four different types of carbon allotrope based nanosystems and summarizes the results of recent studies that are likely to have applications in cancer theranostics. We discuss the applications of these nanosystems for cancer imaging, drug delivery, hyperthermia, and PDT/TA/PA. Abstract : One of the major challenges in our contemporary society is to facilitate healthy life for all human beings. In this context, cancer has become one of the most deadly diseases around the world, and despite many advances in theranostics techniques the treatment of cancer still remains an important problem. With recent advances made in the field of nano-biotechnology, carbon-based nanostructured materials have drawn special attention because of their unique physicochemical properties, giving rise to great potential for the diagnosis and therapy of cancer. This review deals with four different types of carbon allotrope including carbon nanotubes, graphene, fullerenes and nanodiamonds and summarizes the results of recent studies that are likely to have implications in cancer theranostics. We discuss the applications of these carbon allotropes for cancer imaging and drug delivery, hyperthermia, photodynamic therapy and acoustic wave assisted theranostics. We focus on the results of different studies conducted on functionalized/conjugated carbon nanotubes, graphene, fullerenes and nanodiamond based nanostructured materials reported in the literature in the current decade. The emphasis has been placed on the synthesis strategies, structural design, properties and possible mechanisms that are perhaps responsible for their improved theranostic characteristics. Finally, we discuss the critical issues that may accelerate the development of carbon-based nanostructured materials for application in cancer theranostics.